PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR KONSUMEN PRIMER YANG TERDAFTAR DI BEI TAHUN 2021 - 2024 - Karine Claudia Willington; Nina Purnasari; Handayani; Rini Herliani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study was conducted to analyze the impact of profitability, liquidity, solvency, and managerial ownership on firm value in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was employed, with the population comprising consumer goods manufacturing companies listed on the IDX during the 2021–2024 period. The sample consisted of 38 companies, each observed over four financial reporting periods, resulting in a total of 152 data points. The sample was selected using a purposive sampling technique based on predetermined criteria to ensure relevance and consistency with the research objectives. Data collection was carried out through questionnaires and documentation studies, allowing for a comprehensive understanding of financial and ownership structures within the companies.The data were analyzed using multiple linear regression, including classical assumption tests such as normality, multicollinearity, and heteroscedasticity, as well as hypothesis testing, all processed using SPSS software. The findings indicate that, partially, profitability and liquidity have a positive and significant influence on firm value. However, solvency and managerial ownership do not have a significant partial effect. The simultaneous F-test revealed that all independent variables—profitability, liquidity, solvency, and managerial ownership—jointly influence the dependent variable, namely firm value. This research contributes to a deeper understanding of the financial and ownership determinants of firm value and provides insights for investors, policymakers, and company management in the primary consumer goods sector